IMPLEMENTASI KEBIJAKAN PENJAMINAN MUTU MADRASAH DI CIANJUR - Aguslani Aguslani (Balai Diklat Keagamaan Bandung, 2022)
The purpose of this study is to identify the implementation of management standard policies in quality assurance for Madrasah in Cianjur Regency. The approach used is descriptive qualitative with research techniques of observation, interviews, and documentation studies. Data collection was carried out through orientation, exploration, and member checks. The results showed that the implementation of madrasah management and quality assurance standards were quite optimal. It could be seen from the activities of planning programs, implementing programs, conducting program monitoring and evaluation as well as implementing effective leadership, constraints and solutions. Madrasas are quite capable of implementing management standards correctly although there are still many shortcomings, including, routine management activities, formalities, low awareness of the importance on quality, lack of regulation understandings, finance activities, and availability of facilities-infrastructure. The madrasas are respectively pesantren-based strategic places, collaboration ability to involve with the community, principal’s effective leadership, and high enthusiasm to improve the madrasah’s quality through implementing education management standards.Keywords: implementation; education management standards; madrasa quality